Fried spicy Linnaeus—the consequences of indiscriminate citation of authors of scientific names - Kottelat, Maurice (Zootaxa, 2015)
Field work provides biologists with opportunities not only to observe and collect the organisms needed for their research, but also to collect information on the use of natural resources. Among ichthyologists, the most common method for the latter is probably culinary exploration. As a fish taxonomist, one of the most surprising offers I have ever had was to eat "Linnaeus". At first glance this sounded like the parricidal and canibalistic resolution of a taxonomic oedipus complex.